2019
DOI: 10.1111/jsbm.12450
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility as a Strategic Opportunity for Small Firms during Economic Crises

Abstract: The aim of this study is to analyze if there is a direct causal relationship between small firms' orientation toward corporate social responsibility and their competitive success, mediated by innovation and performance. A structural equation model has been applied to a sample of 758 small Spanish firms. The results indicate that, in times of economic crisis, socially responsible strategies are a determining factor in firms' competitiveness. Pragmatic advice for practitioners derives from research results, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 145 publications
(180 reference statements)
3
37
0
1
Order By: Relevance
“…En torno a la RSE, son destacables aquellos trabajos que profundizan en las pequeñas y medianas empresas, analizando el papel tan relevante que este tejido empresarial juega en las regiones y países (Gallardo- Vázquez et al, 2013;Gallardo-Vázquez et al, 2014a, 2014bHerrera-Madueño et al, 2016a, 2016bLeón, Benavides y Castán, 2017;Moneva-Abadía et al, 2018;Valdez-Juárez et al, 2018); por otro lado, trabajos que analizan la RSE en el contexto de las empresas cooperativas, vinculando la actuación socialmente responsable con otras acciones tales como la innovación, certificación, premios recibidos, reputación y performance (Castilla-Polo et al, 2018); igualmente, trabajos que analizan la RSE en el sector turismo, tal como se observa en Font, Guix y Bonilla-Priego (2016), Martínez y Nishiyama (2017) y Tyrrell, Paris y Biaett (2012); así como investigaciones que orientan la RS en el contexto de las instituciones de enseñanza superior.…”
Section: Responsabilidad Social Empresarial Y Responsabilidad Social unclassified
“…En torno a la RSE, son destacables aquellos trabajos que profundizan en las pequeñas y medianas empresas, analizando el papel tan relevante que este tejido empresarial juega en las regiones y países (Gallardo- Vázquez et al, 2013;Gallardo-Vázquez et al, 2014a, 2014bHerrera-Madueño et al, 2016a, 2016bLeón, Benavides y Castán, 2017;Moneva-Abadía et al, 2018;Valdez-Juárez et al, 2018); por otro lado, trabajos que analizan la RSE en el contexto de las empresas cooperativas, vinculando la actuación socialmente responsable con otras acciones tales como la innovación, certificación, premios recibidos, reputación y performance (Castilla-Polo et al, 2018); igualmente, trabajos que analizan la RSE en el sector turismo, tal como se observa en Font, Guix y Bonilla-Priego (2016), Martínez y Nishiyama (2017) y Tyrrell, Paris y Biaett (2012); así como investigaciones que orientan la RS en el contexto de las instituciones de enseñanza superior.…”
Section: Responsabilidad Social Empresarial Y Responsabilidad Social unclassified
“…The final cluster with 10% of the references is characterized by studies that analysed the relationship between CSR and performance in SMEs. Previous research has empirically shown that CSR activities in SMEs are a potential driver of a company's performance [63,80,81] and that this positive and significant relationship in micro, small, and medium-sized enterprises is moderated by the size of these organizations; the larger the size, the stronger the relationship [82]. There are also studies that consider this relationship to be partial [59] or even positive but weak [83].…”
Section: Cluster 4: Social Responsibility Practices and Performance Imentioning
confidence: 99%
“…As an essential part of responsible innovation strategies, the stakeholders identified in the literature are: Customers, employees, environment, suppliers, community, owners/shareholders, R&D, government, competitors, funding agencies/investors, and alliances [15,18,20,21,32,38,41,43,44,48,49,[51][52][53]59,62,63,68,69,80,81,85,86,[91][92][93]96,99,103,104,[106][107][108].…”
Section: Responsible Innovation Antecedents and Enablersmentioning
confidence: 99%
“…Those works that delve into small and medium-sized companies are noteworthy, analyzing the relevant role that this business fabric plays in regions and countries (Gallardo-Vázquez et al, 2013;Gallardo-Vázquez et al, 2014a, 2014bHerrera -Madueño et al, 2016a, 2016bMachová et al, 2016;León et al, 2017;Moneva-Abadía et al, 2018;Valdez-Juárez et al, 2018;Appiah et al, 2019). In small and medium-sized enterprises-especially microenterprisesowners who are also managers focus primarily on solving day-to-day ISSN 2071-789X…”
Section: Literature Reviewmentioning
confidence: 99%